Bicondylar Tibial Plateau Fractures: A Critical Analysis Review. Issue 2 (February 2018) - Lee, Adam K.; Cooper, Seth A.; Collinge, Cory
Abstract : Bicondylar tibial plateau fractures represent a broad category of complex, high-energy injuries associated with a high surgical complication rate. Computed tomography and magnetic resonance imaging aid in diagnosis, classification, and surgical planning and should be considered during the initial evaluation or after provisional stabilization is performed as part of staged treatment. No one classification system has superior descriptive traits or reliability. Simply classifying the fracture as unicondylar (partial articular) or bicondylar (complete articular) is the most reliable approach. Malalignment, especially in the coronal plane, and instability predict poor outcomes and should direct surgical intervention. Articular displacement is less predictive. Dual plating is the most stable type of fixation biomechanically but is associated with soft-tissue complications. Single lateral locked plating is an alternative fixation type for bicondylar fractures without a large posteromedial coronal fracture line. Hybrid external fixators are another means of fixation that avoid large exposures and associated soft-tissue disruption. No one fixation strategy is superior in all cases. Patient and injury characteristics should be evaluated on a case-by-case basis to optimally direct the treatment of these complex injuries.